2021
DOI: 10.1038/s41467-021-25407-8
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the additive-assisted oriented growth of perovskite crystallite for high performance light-emitting diodes

Abstract: Solution-processed metal halide perovskites have been recognized as one of the most promising semiconductors, with applications in light-emitting diodes (LEDs), solar cells and lasers. Various additives have been widely used in perovskite precursor solutions, aiming to improve the formed perovskite film quality through passivating defects and controlling the crystallinity. The additive’s role of defect passivation has been intensively investigated, while a deep understanding of how additives influence the crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
158
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(203 citation statements)
references
References 34 publications
3
158
0
Order By: Relevance
“…[10,12,13,50] The maximum EQEs for perovskite LEDs with standard thin-film LED structures were expected to be around 10-15% due to the relatively large refractive indices of the perovskite EMLs. [50] However, the EQEs of PeLEDs have exceeded 20% [4][5][6][7][12][13][14]50,54,71,72,82,90,91,93] in recent years. Cho et al [50] demonstrated that this enhancement may be partly attributed to photon recycling which could contribute 30-70% of the overall EL, especially for perovskites with large absorption-emission spectral overlaps.…”
Section: Issues Affecting Device Efficiency: Further Discussionmentioning
confidence: 99%
“…[10,12,13,50] The maximum EQEs for perovskite LEDs with standard thin-film LED structures were expected to be around 10-15% due to the relatively large refractive indices of the perovskite EMLs. [50] However, the EQEs of PeLEDs have exceeded 20% [4][5][6][7][12][13][14]50,54,71,72,82,90,91,93] in recent years. Cho et al [50] demonstrated that this enhancement may be partly attributed to photon recycling which could contribute 30-70% of the overall EL, especially for perovskites with large absorption-emission spectral overlaps.…”
Section: Issues Affecting Device Efficiency: Further Discussionmentioning
confidence: 99%
“…Since the first report of perovskitebased LEDs in 2014, [8][9][10] 3D perovskite film-based NIR-I LEDs have been developed using several methods, such as surface passivation and by employing optimum hole-transporting materials, affording external quantum efficiencies (EQEs) of >20% [11][12][13][14] in just a few short years of development. To further improve the image contrast, a narrow full width at half maximum (FWHM) of the emitting light is a key issue for efficiently filtering out the excitation light.…”
Section: Doi: 101002/adma202109785mentioning
confidence: 99%
“…The external quantum efficiencies (EQEs) of PeLEDs increased from 0.76% to 23.4% for green light, 12.3% for blue light, 22.2% for near-infrared light, and the power conversion efficiency (PCE) of PSC also improved from 3.8% to 25.5%, such rapid research progress has undoubtedly promoted the vigorous development of perovskite materials. [1][2][3][4][5][6][7][8] TFB as hole transport layer (HTL) to engineer the charge injection and extraction. We obtained a bifunctional device with an EQE EL of 23.2% with a brightness of 490 W sr −1 m −2 at 2.7 V under PeLED operation and a PVE of 15.2% when operated as PSC.…”
Section: Introductionmentioning
confidence: 99%
“…The external quantum efficiencies (EQEs) of PeLEDs increased from 0.76% to 23.4% for green light, 12.3% for blue light, 22.2% for near‐infrared light, and the power conversion efficiency (PCE) of PSC also improved from 3.8% to 25.5%, such rapid research progress has undoubtedly promoted the vigorous development of perovskite materials. [ 1–8 ]…”
Section: Introductionmentioning
confidence: 99%